Testing the "Zero‐Sum Game" Hypothesis: An Examination of School Health Policies and Practices and Inequalities in Educational Outcomes. (3rd March 2020) - Long, Sara J.; Littlecott, Hannah; Hawkins, Jemma; Eccles, Gemma; Fletcher, Adam; Hewitt, Gillian; Murphy, Simon; Moore, Graham F.
ABSTRACT: BACKGROUND: Health and education are intrinsically linked, while both are significantly patterned by socioeconomic status throughout the life course. Nevertheless, the impact of promoting health via schools on education is seen by some as a "zero‐sum game"; ie, focusing resources on health improvement activity distracts schools from their core business of educating pupils, potentially compromising educational attainment. There is emerging evidence that school health improvement interventions may beneficially influence both health and attainment. However, few studies have examined the relationship between school health improvement activity and socioeconomic inequalities in educational attainment. METHODS: Wales‐wide, school‐level survey data on school health policies and practices was linked with routinely collected data on academic attainment. Primary outcomes included attendance and academic attainment at age 14 (Key Stage 3) and 16 (Key Stage 4). Linear regression models were constructed separately for high and low Free School Meal (FSM) schools, adjusting for confounders. Interaction terms were fitted to test whether there was an interaction between FSM, health improvement activity, and outcomes. RESULTS: There were positive associations between almost all school health variables and KS3 attainment among high, but not low FSM schools. Similarly, for attendance, there were positive associations of several health variables among high but not low FSM schools. There were no associations for KS4 attainment. CONCLUSIONS: Our findings did not support the "zero‐sum game" hypothesis; in fact, among more deprived schools there was a tendency for better attendance and attainment at age 14 in schools with more embedded health improvement action.